A Contemporary Process To Escalate [Mn C] Quotient Of High Carbon Ferromanganese - P. J. Bhonde; R. D. Angal; R. H. Tupkary (The Southern African Institute of Mining and Metallurgy, 2007)
Manganese imparts numerous beneficial mechanical properties. Hence it finds extensive application in iron, steel and non-ferrous sector. Prevalently, it is incorporated in the form of master alloys i.e. 'ferromanganese'. In India, ferromanganese is mainly the inexpensive and paramount source of availability of manganese. Various conventional and non-conventional techniques of ferromanganese production have been adopted in past and present. However, these techniques have demerits viz. high refractory, energy consumption, losses of valuables in slag and fumes. Also geographical co-ordinates of the plant restricted the manufacturer to prefer an appropriate process. Accordingly, the industrially implemented methods had reliance on availability of infrastructure, energy, mineral resources, grade of raw material, outlay of labor, environmental compatibility of technique etc. In view of the liberalized economy and the gap scenario in the supply and demand of ferromanganese, the authors felt it indispensable to explicitly bridge up this vacuum by initially designing a simple energy conserving, eco-friendly, low capital investment technique for decarburization of ferromanganese. Measurement of the data involved studying the impact of rate governing parameters on the process kinetics. This laboratory scale investigation is expected to escalate the Mn/C quotient of high carbon ferromanganese. Key Words: ferromanganese, carbon, carbide, decarburization, rate, kinetic